On the Design of Wide FoV Angle Diversity Receivers for Vehicle-to-Vehicle VLC - Barrios, Alejandro Lopez; Morales-Cespedes, Maximo (IEEE Vehicular Technology Conference, 2024)
Visible light communication (VLC) has been re-cently proposed for enabling high bandwidth datalinks in ve-hicular scenarios (V-VLC). Due to the particular geometrical characteristics of the datalink between vehicles, wide field of view (Fo V) and high optical gain are required for guaranteeing reliable communications. To achieve these features while providing high modulation bandwidth the design of angle diversity receivers (ADRs), which basically are composed of a set of photodiodes following an angular arrangement is considered in this work. Specifically, two design approaches based on hemispherical lenses and compound parabolic concentrators are analyzed considering the dimensional constraints of the ADRs. Simulation results show that CPC-based ADRs obtain a greater trade-off between optical gain and Fo V subject to higher dimensional constraints.